Big Hero 6 [videorecording (Blu-Ray + DVD)] - Jackman, Henry (Henry Pryce) (Disney DVD., 2019)
Robotics genius Hiro Hamada and his personal companion robot, Baymax, must band together with their friends to save San Fransokyo.